(untitled) (International Journal of Food and Nutritional Sciences, 2021)
Maya Angelou’s poetry is a profound exploration of identity and empowerment, intertwining personal experience with universal themes of resilience, race, and gender. Her works, such as Still I Rise, Phenomenal Woman, and Caged Bird, serve as powerful affirmations of self-worth and resistance, challenging societal oppression and celebrating the human spirit’s indomitable nature. Angelou’s exploration of identity delves into the intersectionality of race, gender, and individuality. Her poetry vividly reflects the struggles of African Americans, especially women, against the legacies of slavery and systemic racism. Poems like Caged Bird use metaphor and imagery to depict oppression while affirming hope and the desire for freedom. Simultaneously, works like Phenomenal Woman redefine beauty and femininity, embracing confidence, strength, and individuality in defiance of societal norms. Empowerment is a recurring theme throughout Angelou’s poetry, rooted in resilience and self-love. In Still I Rise, the speaker’s defiant tone and repetition underscore an unyielding determination to overcome adversity. Angelou also emphasizes the collective aspect of empowerment, advocating for justice and unity in works like On the Pulse of Morning. Spirituality and historical memory further enrich her narratives, connecting personal growth with communal progress.